Prevalence and multilocus genotyping of Giardia duodenalis in Holstein cattle in Yunnan, China - Heng, Zhao-Jun; Yang, Jian-Fa; Xie, Xin-Yan; Xu, Cui-Rong; Chen, Jun-Rong; Ma, Jun; He, Jun-Jun; Mao, Hua-Ming (Frontiers in Veterinary Science, 2022)
Giardia duodenalis is an important zoonotic protozoon, which can infect a variety of animals, causing diarrhea and even death of animals or humans. Dairy cattle have been implicated as important sources of human G. duodenalis. However, the information about the prevalence and genetic diversity of G. duodenalis in dairy cattle in China's Yunnan Province remains limited. This study investigated the occurrence and multilocus genotyping of G. duodenalis of Holstein cattle in Yunnan Province, China. A total of 524 fresh fecal samples of Holstein cattle were randomly collected from 8 farms in Yunnan. In this study, 27.5% (144/524) of tested samples were positive for G. duodenalis infection. The highest infection ratio was found in preweaned calves (33.7%), and the infection rates of postweaned calves, growing cattle, and adult cattle were 24.5%, 23.0%, and 17.3%, respectively. The sequence analysis of SSU rRNA gene showed that the predominant assemblage of G. duodenalis in this study was assemblage E (97.9%, 141/144), whereas assemblage A was identified only in three samples (2.1%, 3/144). All G. duodenalis-positive samples were further assayed with nested polymerase chain reaction (PCR) targeting β-giardin (bg), triosephosphate isomerase (tpi), and glutamate dehydrogenase (gdh) genes, and 87, 41, and 81 sequences were obtained, respectively. Mixed infection of assemblages A and E of G. duodenalis was detected in three samples. Multilocus genotyping yielded 23 multilocus genotypes (MLGs). This is the first study that reveals the prevalence data of G. duodenalis in Holstein cattle in Yunnan Province, and the results of this study provided baseline data for the prevention and control of G. duodenalis infection in Holstein cattle in Yunnan Province, China.